Impact of Theory of Planned Behavior on Financial Satisfaction Based on Fintech Performance - Rowena, Janny; Usman, Bahtiar; Lestari, Henny Setyo (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The rapid development of financial technology (fintech) has significantly transformed the way individuals manage their financial activities, influencing not only their financial behaviors but also their overall financial satisfaction. Grounded in the Theory of Planned Behavior (TPB), this study aims to investigate the influence of behavioral factors including attitude attitude toward fintech, subjective norm on herding, perceived overconfidence on financial satisfaction based on fintech performance with intention to use fintech for investment as mediating variable. The study employs a quantitative research design using a survey method with a sample of 400 university students in Indonesia, representing the millennial and Generation Z demographic groups who are among the most active fintech users. Data were analyzed using Structural Equation Modeling (SEM) to test the hypothesized relationships among variables. The findings highlight that university students’ financial satisfaction in fintech investments is not solely determined by technological factors but by the interaction between attitude, social influence, confidence, and actual behavioral engagement. Positive attitudes and peer-driven norms enhance fintech adoption and satisfaction only when accompanied by meaningful usage and effective fintech performance. Conversely, overconfidence without competence may hinder satisfaction despite technological accessibility.